The Role Information Technology in Increasing the Effectiveness Accounting Information Systems and Employee Performance - Aoliyah Firasati; Fadhila Azzahra; Sausan Raihana Putri Junaedi; Amelia Evans; Muchlisina Madani; Fitra Putri Oganda (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2024)
This study explores the mportant role of Information Technology (IT) in enhancing the effectiveness of Accounting Information Systems (AIS) and improving employee performance, using a moderator analysis approach. The context of the study is the increasing dependence of modern organizations on AIS for accurate financial data management and decision-making. However, the effectiveness of these systems can be influenced by various factors, including technological advancement and employee skills. The research methodology includes quantitative analysis, using survey data from various organizations in different sectors. Structural equation modeling (SEM) was applied to examine the moderating effect of IT on the relationship between AIS effectiveness and employee performance. The results of the study show a significant positive impact of IT on AIS effectiveness, leading to increased employee performance. These findings contribute to the literature by highlighting the importance of IT interventions in optimizing AIS functionality, thereby improving organizational efficiency and productivity. In conclusion, this study highlights the essential role of IT as a supporting tool to achieve higher levels of efficiency in accounting information systems and employee performance and highlights the need for continued technological advancement and employee training in the modern business environment.